2015
DOI: 10.4236/aim.2015.512081
|View full text |Cite
|
Sign up to set email alerts
|

Detection of <i>Chlamydia trachomatis</i> and <i>Neisseria gonorrhoeae</i> in Egyptian Women Suffering from Infertility

Abstract: Chlamydial and gonococcal infections are recognized as two of the major causes of sexually transmissible human bacterial infection which may lead to infertility. In this cross sectional study, we aimed to determine the prevalence of Neisseria gonorrhoeae, Chlamydia trachomatis among Egyptian women using different microbiological methods. One hundred and fifty cervical swabs were collected, of which 100 were from infertile women. Culture and ELISA technique were used for screening of Neisseria gonorrhoeae and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…Our results are partially in agreement with Elkayl who reported that 2% of gonorrhoeae suspected patients was confirmed through PCR analysis in Egyptian woman [21] .…”
Section: Discussionsupporting
confidence: 93%
“…Our results are partially in agreement with Elkayl who reported that 2% of gonorrhoeae suspected patients was confirmed through PCR analysis in Egyptian woman [21] .…”
Section: Discussionsupporting
confidence: 93%
“…26 In infertile females, lower prevalence rates of 0.4%to 2% were observed. 18,27 In this present study we did not find any subjects with N. gonorrhoeae, similar to the findings by Hazlina et al (2005). 15 In Malaysia, prevalence rates of gonorrhoea were mostly reported among subjects at higher risk for HIV and other STIs such as commercial sex workers (5.8%) 28 and male attendees of genitourinary clinic (24.2%).…”
Section: Neisseria Gonorrheasupporting
confidence: 93%
“…Medical Education (2008) 67 Gdoura et al (2008) 178 Sadrpour et al (2013) 164 Al-Sweih et al (2012) 100 Ahmadi et al (2018) 49 Golshani et al (2007) 155 Dehghan et al (2017) 57 Moazenchi et al 2018159 Total Random effects model Heterogeneity: 93 Al-Ramahi et al (2008) 93 Joolayi et al (2017) 62 Al-Ramahi et al (2008) 93 Rashidi et al (2013) 71 Ahmed (2012) 167 Abdella et al (2015) 144 Hajikhani et al (2013) 156 Al-Ramahi et al (2008) 93 Joolayi et al (2017) 62 Mohammed et al (2017) 90 Siam and Hefzy (2012) 151 Kalantar et al (2007) 157 Gdoura et al (2001b) 177 Alfarraj et al (2015) 174 Dawood (2011) 169 Elkayal et al (2015) 146 Goshayeshi et al (2015) 58 Nada et al (2015) 45 Mousavi et al (2014) 69 Mansour Ghanaie (2014) 158 Marashi et al (2014) 66 Rashidi et al (2013) 71 Dehghan et al (2017) 57…”
Section: Prevalence (95% Ci)mentioning
confidence: 99%